Description of Candida Species Infection on the Skin Between the Fingers of Milkfish Selectors - Mahanani, Zhendyta Elsya; Haryatmi, Dwi (Indonesian Journal of Global Health Research, 2023)
Candidiasis is a fungal infection of the skin caused by the Candida fungus. Candida fungi live in the human body as saprophytes which can be in the digestive tract, respiratory tract and vagina of normal or healthy people. Candida infections on the skin between the fingers most often occur when the hands are repeatedly soaked in water for long periods of time, this occurs in housemaids, cooks, vegetable and fish handlers. The aim of this research was to determine whether there was skin candidiasis infection between the fingers of milkfish sorters in Mojolaban Sukoharjo and what species of Candida were found. The research used a descriptive method with the population of milkfish sorting workers taken by purposive sampling based on criteria in accordance with the objectives of the examination which obtained a total of 14 respondents. Data was taken from the results of questionnaires and skin scraping cultures on CHROMagar-Candida media which were then identified macroscopically and microscopically. The results were presented in tabular form and analyzed descriptively, where 3 of 14 skin scraping samples from milkfish sorters in Mojolaban Sukoharjo were found (positive) to be infected with Candida krusei.